Adverse Incident Reporting and Staff Vigilance Leads to Early Identification of Medical Equipment Problems - Ramirez, Mario R; Niles, Eric; Virdi, Navtej; Yang, Rocky; Patterson, Greg (CMBES Proceedings, 2016)
Adverse Incident reporting has become a standard of practice at SickKids. When staff experience an adverse event they are encouraged to file an Incident Report. The Incident report system generates e-mails to people who need to be aware of the incident. When medical equipment is involved, Medical Engineering receives the Incident Report. Staff are asked to clearly identify the device that and send it to Medical Engineering. In August 2015, we received two incidents where a Syringe Module stopped working with a channel error message. The incidents happened in the Paediatric Intensive Care Unit (PICU). Testing of the Syringe module indicated that the module was working properly. A third incident occurred in the same unit. The QA leader for the PICU contacted Medical Engineering’s Team leader to identify possible trends. Upon investigation, it was determined that the Channel Error was only being experienced in the PICU. We received a fourth incident with the same reported problem. Biomedical Engineering Technologists performed extended testing by simulating similar infusion as reported by nurse. This time the Technologists did duplicate the Channel Error. Upon opening the Syringe Module’s casing, the technologists discovered some traces of oxidation/rust in the drive mechanism. This was suspected to be the cause of the Syringe Module failure. During the month of August we continued to receive Incidents with the same Syringe Module issue. The presentation will cover our findings of oxidation on the drive train, the company’s response and the action plan to inspect and correct 800 Syringe modules.